The effect of chemical variations on the structural polarity of relaxor ferroelectrics studied by resonance Raman spectroscopy. (23rd September 2016) - Rohrbeck, A; de la Flor, G; Aroyo, M I; Gospodinov, M; Bismayer, U; Mihailova, B
Abstract: Resonance Raman spectroscopy was applied to doped PbSc0.5 Ta0.5 O3 and PbSc0.5 Nb0.5 O3 relaxor ferroelectrics, to better understand the effect of composition disorder on the mesoscopic-scale polar order in complex perovskite-type ( AB O3 ) ferroelectrics. The excitation photon energy used was 3.8 eV, which is slightly above the energy gap and corresponds to the maximum of the optical dielectric permittivity. Group-theory analysis reveals that the resonance Raman scattering (RRS) observed under these conditions is allowed only in polar crystal classes. Therefore, RRS is dominated by the atomic dynamics of nanoregions with coherent polar distortions, which considerably facilitates the comparison of polar order in various compounds. The results show that A -site doping (Ba 2+, Sr 2+, La 3+, Bi 3+ ) has significantly stronger effect on the structural polarity than the introduction of a third element at the B site (Nb 5+ or Sn 4+ doped in PbSc0.5 Ta0.5 O3 ). The A -site substitution by cations that in contrast to Pb 2+ have isotropic outermost electron shells disturbs the system of lone-pair electrons, thus reducing the correlation length of coupled polar distortions and the strength of the electric field associated with the mean polarization of polar nanoregions. A -site doping with larger cations (Ba 2+ ) augments the polar deformation of the individual B O6 octahedra due to local elastic fields. As a result, such A -site doping intensifies the initial structural polarity at high temperatures and prevails the enlargement of the polar fraction at low temperatures. A -site doping with smaller cations (Sr 2+, La 3+ ), regardless if they are isovalent or aliovalent to Pb 2+, increases the correlation length of antiferrodistortive order ( B O6 tilts), which in turn assists the development of double-perovskite structure with coherent local polar distortions. A -site doping with aliovalent cations (Bi 3+ ) having the same outermost electron shell and ionic radius as the host A -site Pb 2+ cations leads to stronger coupling along the – B –O– B – bond linkages due to enhanced random local electric fields.